2009
DOI: 10.3899/jrheum.080335
|View full text |Cite
|
Sign up to set email alerts
|

Current Therapies for Lupus Nephritis in an Ethnically Heterogeneous Cohort

Abstract: After controlling for the fact that less severe nephritis is preferentially treated with MMF, we found overall that response to MMF was superior to CYC. In this US population, ethnicity was observed to have an influence on response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 16 publications
2
25
1
Order By: Relevance
“…However, the majority of patients from recent uncontrolled studies were European (1,6,7,9,11,12). This ethnicity is important because some studies have suggested a variable therapeutic response to the main immunosuppressive agents in different ethnic groups (13).…”
Section: To the Editorsmentioning
confidence: 99%
“…However, the majority of patients from recent uncontrolled studies were European (1,6,7,9,11,12). This ethnicity is important because some studies have suggested a variable therapeutic response to the main immunosuppressive agents in different ethnic groups (13).…”
Section: To the Editorsmentioning
confidence: 99%
“…In humans, it was initially used as an induction treatment and subsequently for maintenance therapy, particularly in patients with proliferative LN [21][22][23][24] . Recently it was shown that MMF is also beneficial in membranous LN [25][26][27] . Our group of 35 patients included various LN types, most of whom (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of studies of other primary glomerulopathies, Asian ethnicity may be associated with a relatively favorable prognosis and increased responsiveness to certain immunosuppressive regimens. [77][78][79] A trial from the Netherlands compared outcomes of 32 IMN patients treated with 1 year of MMF plus corticosteroids with historical matched controls treated with oral cyclophosphamide plus corticosteroids for 1 year. 75 Patients were considered at high risk for progressive disease with reduced GFR at baseline (median approximately 40 ml/min) and high-grade proteinuria.…”
Section: Mmfmentioning
confidence: 99%